Learning about banks' net worth and the slow recovery after the financial crisis - Josef Hollmayr; Michael Kühl (Deutsche Bundesbank, 2016)
In this paper, we examine the influence of information rigidities concerning the net worth of banks on the real economy over time. In a first part, we show empirically that expectations about the net earnings of banks (as growth of net worth) are truly biased, particularly during the financial crisis. The forecast error of professional investors cannot be attributed to sticky information but rather to noisy information. Investors display a learning behavior with regard to past forecast errors in forming their expectations about future earnings during the crisis. In a second part, by drawing on a New Keynesian general equilibrium model with a banking sector, we demonstrate that, by quantitatively incorporating this type of information updating and expectations formation about the net worth of banks, noisy information can produce a slow recovery compared to a full information rational expectation case.
Keywords: E3; E44; 330; DSGE Model; Survey Data; Imperfect Information; Learning; Slow Recovery